Implementasi Video Company Profile PT. Sanindo Multi Tekno Dengan Gabungan Cinematic Dan Motion Graphics Menggunakan Metode MDLC - Nehara, Renetha; Amadia, Rini (Politeknik Negeri Batam, 2025)
This study aims to design a company profile video for PT. Sanindo Multi Tekno using the MDLC method with a combination of cinematic and motion graphic techniques. Development was carried out through six stages: Concept, design, material collection, assembly, testing, and distribution. Production involved interviews, storyboarding, material collection, and editing using CapCut Pro and Adobe After Effects. Evaluation was carried out through alpha testing by multimedia experts and validation from the company. Beta testing involved 35 respondents using the AIDA model and brand awareness analysis. The video was distributed through YouTube and Instagram to expand reach and increase the company's brand awareness.